Using XML to Improve Frameworks Reuse - Amaral, Juliana Alves; Pietrobon, Carlos Alberto Marques (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2002)
This paper presents an approach to promote framework exchange through the use of XML standards. This exchange is quite important for developers’ teams who do not work at the same place neither the same environment, but need to collaborate in common projects. This paper combines the benefits of XML for defining, validating and sharing documents on the Web with the benefits of frameworks and object-oriented Unified Modeling Language (UML). UML-F-X, a extension of UML-F (an extension of UML for framework domain), is then proposed in this paper in order to take advantage of DTD concepts, reducing the semantic loss of framework-DTD mapping. By using standards for storing (UML) and sharing (XML) object-oriented frameworks, development teams using tools from multiple vendors can build and reuse applications in a distributed environment. The objective of this approach is to use the Web as a channel to exchange frameworks, stimulating then the use of this object-oriented technique among software engineers.